2016
DOI: 10.1111/jpi.12369
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Melatonin prevents deregulation of the sphingosine kinase/sphingosine 1‐phosphate signaling pathway in a mouse model of diethylnitrosamine‐induced hepatocellular carcinoma

Abstract: The sphingosine kinase (SphK)/sphingosine 1-phosphate (S1P) pathway is involved in multiple biological processes, including carcinogenesis. Melatonin shows beneficial effects in cell and animal models of hepatocellular carcinoma, but it is unknown if they are associated with the modulation of the SphK/S1P system, along with different downstream signaling pathways modified in cancer. We investigated the effects of melatonin in mice which received diethylnitrosamine (DEN) (35 mg/kg body weight i.p) once a week f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 61 publications
(112 reference statements)
3
25
0
Order By: Relevance
“…The pineal hormone melatonin has demonstrated its potential usefulness in the treatment of a number of pathologies, including cancer, where it acts as an effective oncostatic agent . Previous research has shown that this indoleamine exerts antiproliferative, pro‐apoptotic, anti‐invasiveness, and anti‐angiogenic effects in HCC cell lines, and also plays a protective role in murine models of DEN‐induced hepatocarcinogenesis . Evidence from different studies indicates that melatonin and the core clock genes play a crucial role in breast cancer development, and it has been reported that melatonin administration resynchronizes the circadian rhythm in human prostate cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…The pineal hormone melatonin has demonstrated its potential usefulness in the treatment of a number of pathologies, including cancer, where it acts as an effective oncostatic agent . Previous research has shown that this indoleamine exerts antiproliferative, pro‐apoptotic, anti‐invasiveness, and anti‐angiogenic effects in HCC cell lines, and also plays a protective role in murine models of DEN‐induced hepatocarcinogenesis . Evidence from different studies indicates that melatonin and the core clock genes play a crucial role in breast cancer development, and it has been reported that melatonin administration resynchronizes the circadian rhythm in human prostate cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…S1P is formed by phosphorylation of sphingosine in a process catalyzed by two distinct SphKs, and once formed may be irreversible degraded by S1PL to hexadecenal and phosphoethanolamine [25]. SphK1 is overexpressed in colon of IBD patients and in mice with DSS-induced colitis, and mice lacking SphK1 are less susceptible to experimentally induced IBD [26].…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenesis—or tumorigenesis—is a pathological alteration of epithelial/mesenchymal cells under the stimulation of risk factors, namely, the epithelial–mesenchymal transformation (EMT) . This process is characterized by alterations at the cellular, genetic, and epigenetic levels and abnormal cell division.…”
Section: Foxo1 and Carcinogenesismentioning
confidence: 99%